Electrocatalysis of S-doped carbon with weak polysulfide adsorption enhances lithium–sulfur battery performance. Issue 45 (3rd May 2019) - Du, Lingyu; Cheng, Xueyi; Gao, Fujie; Li, Youbin; Bu, Yongfeng; Zhang, Zhiqi; Wu, Qiang; Yang, Lijun; Wang, Xizhang; Hu, Zheng
Abstract : S-doped carbon boosts the conversion of lithium polysulfides by electrocatalysis as revealed by kinetic analysis and theoretical calculation, which suppresses the serious polarization effect and thus enhances the Li–S battery performance, despite its weak adsorption to polysulfides. Abstract : Heteroatom-doped nanocarbons are beneficial for the performance improvement of lithium–sulfur batteries, and the reason is usually attributed to their strong adsorption to the soluble polysulfides. Herein, we found that, despite the weak polysulfide adsorption on hierarchical S-doped carbon nanocages (hSCNCs), the hSCNC-encapsulated sulfur cathode still exhibited better performance than the counterpart using undoped carbon nanocages, showing a high capacity of 579 mA h g −1 at 2 A g −1 after 400 cycles, and a high areal capacity of 4.7 mA h cm −2 with a high sulfur loading of 4.5 mg cm −2 . The electrocatalysis-promoted mechanism of S-doped carbon was demonstrated, which facilitated polysulfide conversion and suppressed the polarization effect, thereby leading to superior performance.